Sosialisasi Pencegahan Perundungan Siber pada Siswa-Siswi SMAN 1 Parigi Pangandaran Kelas XIPA1 dan XIPA2 - Dwi Masrina; Linda Kurniawati; Rinda Aunillah Sirait (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The socialization of cyberbullying prevention aims to increase awareness of Pangandaran students about the dangers of cyberbullying and to increase their understanding of the digital culture and ethics of Pangandaran students. The activity was carried out using the lecture method and interactive question and answer. From the results of testing the pre-test and post-test data to measure participants' understanding of the socialization material delivered by the team, it was found that the socialization of cyberbullying prevention increased participants' knowledge about cyberbullying practices.